Analisis Ukuran Perusahaan Dan Profitabilitas Terhadap Kualitas Laba Pada Perusahaan Sektor Industri Dan Kimia Di Bursa Efek Indonesia (Bei) - Khorida SE. AR (Universitas Muhammadiyah Tangerang, 2021)
This research analyze the effect of Firm Size and Profitabilityon Earnings Quality in Manufacturing Companies in the Basic Industry and Chemical Sector 2016-2020. The research was conducted using a quantitative approach. The population in this study were basic industrial companies and chemicals listed on the Indonesia Stock Exchange (BEI) for the 2016-2020 period. The sampling technique used was purposive sampling, the samples obtained were 21 companies with 5 years of observation time, so the research data were 105 data. The analysis technique used is panel data regression with the help of E-Views 9.0 software. This study uses secondary data obtained from the website http://www.idx.co.id.The results show partially that firm size (SIZE) has a positive effect on earnings quality as evidenced by the t-statistic (2.079280)> t Table (1.98422) and the Prob value. (0.0402) <(0.05). And Profitability (ROA) t-statistic (-0.315333) < t Table (1.98422) and the Prob value. (0.7532)> (0.05). Keywords: Firm Size, Profitability, and Quality of Income